Pemanfaatan Daun Bangun-Bangun dalam Pengembangan Produk Makanan Tambahan Fungsional untuk Ibu Menyusui - Hidayat Syarief; Rizal Martua Damanik; Tiurma Sinaga; Tetty Herta Doloksaribu (Institut Pertanian Bogor, 2014)
Bangun-bangun leaves (Coleus amboinicus Lour) is one of plants that has a function as laktagogue which can increase secretion and production of breast milk. Therefore, the bangun-bangun leaves are potential to be used as an ingredient in the product development of supplement and functional foods for lactating mothers. The objective of this research is to develop supplement and functional foods for lactating mothers from the bangun-bangun leaves.Two types of products were made with same type and amount of basic material, but different in the amount of bangun-bangun leaves, i.e.120 or 150 g. Results of organoleptic test using 40 lactating mothers as panelists show that the average panelist favorite for both products were not significantly different and altogether all panelists can accept the two products.